Analysis of surface and profile of pits in austenitic stainless steel AISI 310S by optical microscopy - Ribeiro, Rosinei Batista; de Jesus Silva, José Wilson; de Oliveira Hein, Luis Rogerio [UNESP]; Codaro, Eduardo Norberto [UNESP]; Matias, Nelson Tavares (Trans Tech Publications, 2014)
Pit morphology on sensitized 310S stainless steel has been studied using an image processing method based on reflected light microscopy (profile and surface). Salt Spray test has been used to induce the pitting corrosion. Morphological pits character do not depend on sensitization heat treatments here applied. Nucleation rates and growth may be associated with quantity and distribution of chromium carbides. This being so, condition I (heating up to 1065° C during 1 h and air cooling) and condition II (heating up to 1065° C during 1 h and air cooling followed by reheating up to 670°C during 5 h and again air cooling) are the most susceptible to pitting, in particular the first one. In these two conditions, pits are nucleated in grains and in grain boundaries, while in condition III (heating up to 1065° C during 1 h and air cooling followed by reheating up to 620° C during 24 h and again air cooling), pits are preferentially nucleated in boundaries of small grains. Thence, pits usually grow more rapidly in depth than in width, being able to occur partial or total grains separation. Pits are mainly hemispherical, near-hemispherical, near-conical and near-cylindrical without significant geometric transition associated with an increasing exposure period.
Keywords: Austenitic stainless steel; Optical microscopy; Pitting corrosion